Effect of CO2 curing on the long-term performance of oriented cement-bonded boards after wet-dry cycles - Cabral, Matheus R.; Nakanishi, Erika Y.; Santos, Sérgio F. [UNESP]; Fiorelli, Juliano (Springer Nature, 2025)
This study evaluates the influence of CO2 curing on oriented cement-bonded boards’ long-term performance. The boards used hardwood (Eucalyptus spp.) and softwood (Pinus spp.) strands. After being manufactured and aged for 24 h, the boards undertook two curing processes: control curing and CO2 curing for 12 h, followed by saturation until the 28th day. Subsequently, the boards underwent rigorous testing, enduring 100 wetting and drying cycles. The study assessed hardwood and softwood boards’ physical and mechanical properties according to international standards. Thermal and mineralogical analyses showed that CO2 curing reduced calcium hydroxide content while increasing the boards’ calcium carbonate content. The results indicated that CO2 curing significantly improved the boards’ physical and mechanical properties. Even after undergoing 100 wetting and drying cycles, the CO2-cured boards met ISO 8335 recommendations for cement boards. Specifically, CO2 curing increased the modulus of rupture by 119% for hardwood and 72% for softwood boards, while the modulus of elasticity values exhibited a substantial rise of 179% for hardwood and 121% for softwood boards. These findings demonstrate CO2 curing’s potential to enhance the durability of oriented cement-bonded boards.
Keywords: Calcium carbonate; Calcium hydroxide; Carbonation; Composites; Exposure conditions; Hardwood; Long-term properties; Softwood